Model Integrasi Sistem dengan Pendekatan Metode Service Oriented Architecture dan Model View Controller pada Pusat Penelitian Perkembangan Iptek Lembaga Ilmu Pengetahuan Indonesia - Warkim Warkim; Dana Indra Sensuse (Maranatha University Press, 2017)
The administration management as an activity and institute’s main task which is also called as Back Office System, supported by several information systems. The data need and information in one information system cannot be fulfilled only by one information source, but it needs a composition from a two or more sources in one institute/organization. To solve this problem, we need an architecture model which can solve integration system between different information systems. This Integrated Information System Design Research Method uses Service Oriented Architecture (SOA) approach as the architecture base, Model View Controller (MVC) method as the model in the programming (coding). The applied development method SOA utilizes Service Oriented Modelling and Architecture (SOMA) development system, it is a system design method which classifies business process in to a service group. The SOA application is because of its loosely coupled, highly interoperable, reusable and interoperability characteristics cause SOA reliable in information development and integration. While the integrated information system which is built using MVC method, easier to be maintained and developed. This research produce employment service, asset service, supplies service, financial service and also system prototype as a dashboard for employment service with SOA approach and MVC method which uses Representational State Transfer (REST) technology